Courtship activity, copulation & insemination success in a mosquito vector fed a herbal aphrodisiac: Implications for sterile insect technology - Hamady, Dieng; Fatimah, Abang; Fatin, A.B. Azman; Nurshilawati, Abdul Latip; Nur Ezzati, Aliasan; Sabina, Noor; Cirilo Nolasco, Nolasco-Hipólito; Tonga, Noweg (Medknow Publications, 2018)
Background & objectives: In sterile insect technology (SIT), mating competitiveness is a pre-condition for the reduction of target pest populations and a crucial parameter for judging efficacy. Still, current SIT trials are being hindered by decreased effectiveness due to reduced sexual performance of released males. Here, we explored the possible role of a herbal aphrodisiac in boosting the mating activity of Aedes aegypti. Methods: Males were fed one of two diets in this study: experimental extract of Eurycoma longifolia (MSAs) and sugar only (MSOs). Differences in life span, courtship latency, copulation activity and mating success were examined between the two groups. Results: No deaths occurred among MSA and MSO males. Life span of MSOs was similar to that of MSAs. The courtship latency of MSAs was shorter than that of MSOs (P<0.01). MSAs had greater copulation success than MSOs (P<0.001). In all female treatments, MSAs mated more than MSOs, but the differences in rate were significant only in the highest female density (P<0.05). In MSAs, mating success varied significantly with female density (P<0.01), with the 20-female group (P<0.01) having the lowest rate. Single MSA had better mating success at the two lowest female densities. In MSOs, there were no significant differences in mating success rate between the different female densities. Interpretation & conclusions: Our results suggested that the herbal aphrodisiac, E. longifolia, stimulated the sexual activity of Ae. aegypti and may be useful for improving the mating competitiveness of sterile males, thus improving SIT programmes.